A data-driven waterway simulation model for inland waterway operation. (13th February 2008) - Wang, Shiaau-Lir
A waterway network can be characterised as a large queuing system with features of two-way traffic, tow variations, chamber assignment, and tow sequencing. Since no analytical model is fully sufficient to analyse the system's complexity, a data-driven waterway simulation model is developed to evaluate the overall performance of any particular operational and investment plan by considering network interdependencies. The proposed model is verified with analytical queuing theory, and validated with available real world data. The model's portability and functionality are demonstrated through different network scenarios, various control alternatives for lock operations, and dynamic demand for traffic interactions.